النظام القانوني لحوادث السكك الحديدية - - بلهادف أحمد عمار - غربي سليمان (جامعة المسيلة, 2021)
مهما حاولنا الإلمام بالنظام القانوني لحوادث السكك الحديدية، نصطدم دائما بالتشعب وقلة المصادر واختلاف طريقة الدول وتعاملها مع هذا النوع من الحوادث، فكل دولة لها طرقها ونظامها الخاص ونحن في بلادنا استمدينا تجربتنا هذه من فرنسا وهذا بسبب الإرث التاريخي للاستعمار، وتعامل الفقه والقضاء بالارتكاز على التجربة الفرنسية وكان بحثنا هذا مواكبا لهذه التجربة، وتم التركيز على أنواع المسؤولية والأساس القانوني لها وطرق الدفع فيها مع التطرق إلى نظام التعويض وتمنينا أن نكون قد اجبنا على هاته التساؤلات في هذا البحث. No matter how we try to familiarize ourselves with the legal system of railway accidents, we always encounter the complexity and the lack of sources and the different ways countries deal with this type of accident. each country has its own methods and system. we in our country have derived our experience from France. this is because of the historical legacy of colonialism. jurisprudence and the judiciary are treated on the basis of the French experience. our research has been consistent with this experience. we have focused on the types of liability, the legal basis and the methods of payment therein, with regard to the compensation system. we wish to have answered these questions in this research.
Keywords: حوادث -السكك الحديدية